Anisotropy visualisation from X-ray diffraction of biological apatite in mixed phase calcified tissue samples - Scott, Robert; Lyburn, Iain D.; Cornford, Eleanor; Bouzy, Pascaline; Stone, Nicholas; Greenwood, Charlene; Gosling, Sarah; Arnold, Emily; Bouybayoune, Ihsanne; Pinder, Sarah E.; Rogers, Keith (Springer, 2025)
X-ray diffraction is widely used to characterise the mineral component of calcified tissue. Broadening of the diffraction peaks yields valuable information on the size of coherently diffracting domains, sometimes loosely described as crystallite size or crystallinity. These domains are markedly anisotropic, hence a single number describing their size is misleading. We present a novel variation on a method for visualising crystallographic anisotropy in X-ray diffraction data. This provides an intuitively interpretable depiction of crystalline domain size and anisotropy. The new method involves creating a polar plot of calculated domain thickness for peaks in a diffractogram versus crystallographic direction. Points with the least error are emphasised. Anisotropic domain dimensions are calculated by refining an ellipsoidal model in a whole pattern fit. These dimensions are then used to overlay an ellipse on the peak broadening plot. This is illustrated by application of the method to calcifications in breast tissue with suspected cancer, which frequently contain whitlockite as well as nanocrystalline apatite. Like most biogenic apatite, this exhibits markedly anisotropic peak broadening. The nature of this anisotropy offers potentially useful information on normal function and pathology of calcified tissue and is a frequently neglected crystallographic feature of these materials.
Keywords: X-ray diffraction; Apatite; Hydroxyapatite; Whitlockite; Anisotropy